2014
DOI: 10.1016/j.proeng.2014.10.332
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Eccentricity on Movements of Orbital Head with Double Eccentric Structure in Orbital Forging

Abstract: An orbital head of orbital forging press with double eccentric sleeve has four types of movement, but most workpieces are formed by circular movement. The motion equation is established according to the structure and the movement principle of orbital head. Then find that the rotational speed of inner and outer eccentric sleeves simply affects the rotation period of orbital head in circle and straight line movements, and not only affects the rotation period but also the movement shape in spiral and rose curve m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The torque of the motor is transmitted to the eccentricity rings by power transfer shafts. Cross sections of both ends of the output shafts will produce relative rotation under the torsion couple, where u represents the relative torsional angle, which can be calculated by equation (10).…”
Section: Horizontal Dynamic Model Of the Cof Machinementioning
confidence: 99%
See 1 more Smart Citation
“…The torque of the motor is transmitted to the eccentricity rings by power transfer shafts. Cross sections of both ends of the output shafts will produce relative rotation under the torsion couple, where u represents the relative torsional angle, which can be calculated by equation (10).…”
Section: Horizontal Dynamic Model Of the Cof Machinementioning
confidence: 99%
“…7 Regarding COF kinematics, Han et al 8,9 revealed the kinematic mechanism of the COF machine and obtained kinematic equations of the COF machine. Feng et al 10 and Dong et al 11 presented the influence of structural parameters on the kinetic locus of a COF machine. Regarding the COF application, [12][13][14][15] investigated applications of COF in manufacturing spur bevel gears, gear racks, and rings.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25] investigated some effective structure optimization methods for improving the performance of machines. However, investigations into the COF machine are mainly investigations of the deformation mechanism, forging force and kinematic mechanism of COF [26][27][28][29][30][31][32][33], and few investigations into the static performance and dynamic performance of the COF machine have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of kinetic locus of the upper tool, Hu and Che [24] analyzed the kinetic locus of the upper tool in PXW cold orbital forging machine. Feng et al [25] examined the influences of eccentricity of two eccentricity rings on the kinetic locus of the upper tool. However, the above researches only aimed at the kinetic locus of one point in the axis of the upper tool, while the researches on the kinetic locus of one point in the working surface of the upper tool were scarce.…”
Section: Introductionmentioning
confidence: 99%